Pengembangan E-Modul Berbasis SETS (Science, Environment, Technology, and Society) Pada Materi Inovasi Teknologi Biologi untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas X SMA/MA - Zahrah, Thifal; Idramsa,; Lubis, Khairiza (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to describe the validity, teacher responses, student responses, practicality, effectiveness, and the improvement of critical thinking skills through the development of a SETS-based. This study employed a Research and Development (R&D) approach using the 4D model. The results show that: (1) The validity of the SETS-based e-module is categorized as very feasible, with an average score of 85% for material validation, 95% for media validation, and 89% for language validation, indicating that the e-module is suitable for instructional use. (2) Teacher responses indicate that the SETS-based e-module helps students develop more comprehensive and contextual thinking, the average score obtained for the model design aspect was 85%, the concept mastery aspect was 90% and the learning motivation aspect was 88%. (3) Student responses demonstrate that the e-module meets the criteria of practicality, comfort, and usefulness, and successfully enhances learning interest and motivation. The results obtained for the module design aspect were 95%, the concept mastery aspect was 89% and the learning motivation aspect was 90%. (4) The practicality and effectiveness tests reveal an average score of 91%, placing the e-module in the highly practical and highly effective categories for learning. (5) The improvement of students’ critical thinking skills is evidenced by the t-test 0.05, which indicates a significant difference between pretest and posttest scores. The average N-Gain score of 0.758, categorized as high, shows that the SETS-based e-module increased students’ critical thinking ability by 76%. Overall, the developed SETS-based e-module is valid, practical, effective, and capable of significantly improving students’ critical thinking skills.